USER AWARENESS, IMPEDIMENTS AND PROPOSED IMPROVEMENTS TO THE ONE STOP CENTRE (OSC) ONLINE 3.0 SYSTEM. CASE STUDY: MUNICIPAL COUNCIL OF SUBANG JAYA, SELANGOR, MALAYSIA - Kamaruddin, Siti Mazwin; Mohd Rosmi, Rozdiana; Muhamad Halil, Faridah; Misni, Alamah; Marzukhi, Marlyana Azyyati (PLANNING MALAYSIA, 2020)
This study provides an insight into an adoption of online submission approach at a planning stage. The case study is an implementation of One Stop Centre (OSC) Online 3.0 System at a Local Authority. Local Authority is Majlis Perbandaran Subang Jaya (MPSJ) as one of the pioneers to implement this system. Currently, not all Local Authorities implement the system fully. For this study, the data collected consisted of primary and secondary data. Primary data of users’ knowledge, readiness and satisfaction of the system were collected through a survey in a form of questionnaire. In contrast, secondary data were acquired from Local Government Department, MPSJ OSC Department and reliable sources, such as reports of the development plan, Local Authorities, relevant agencies, and websites. The findings indicated that almost half of the users found the system effective and successful while suggesting that there was still room for improvement relevant in shaping the alignment between technology, organisation and human factor. The resulting knowledge from this study could help to improve e-government implementation in Malaysia and could benefit other Local Authorities towards digital e-submission of plans online.